Indian Herbal Bioenhancers: A Review - Singh, Ratndeep; Devi, Sarita; Patel, Jatin H.; Patel, Urvesh. D.; Bhavsar, Shailesh K.; Thaker, Aswin M. (Pharmacognosy Reviews)
Herbal bioenhancers are phytomolecules that at low doses promote and augment the bioavailability or biological activity of drugs. Their development is based on ancient knowledge of Ayurveda. They reduce the dose, shorten the treatment period and thus reduce drug-resistance problems. Due to dose-economy, they make treatment cost effective, minimize drug toxicity and adverse reactions. They are effective when used in combination with number of drug classes such as antibiotics, antituberculosis, antiviral, antifungal and anticancerous drugs. They improve oral absorption of wide range of nutrients such as vitamins, minerals, herbal extracts and amino acids. They act through several mechanisms of action affecting mainly absorption process, drug metabolism or action on drug-target. Since, bioavailability of drugs and nutrients is of equal relevant to animal health as for as human health, uses of bioenhancers are also applicable in veterinary practice. This review highlights some of the herbal bioenhancers and their applications in human and veterinary practices.
Keywords: Bioavailability; Drugs; Herbal bioenhancers; Nutrients